RUG PULLS : CLASSIFYING NFT SCAMS AND THE REGULATORY INSTRUMENTS NEEDED IN INDONESIA (INTERNATIONAL SEMINAR, 2025)
The phenomenon of Non-Fungible Token (NFT) trading has grown rapidly and has emerged as a promising new digital economic instrument. However, this development is accompanied by an increasing prevalence of scams within the NFT ecosystem, such as rug pulls, phishing, replay attacks, and falsified copyright claims over digital works. Indonesia currently lacks a regulatory framework that specifically governs NFT transactions or provides legal protection for consumers participating in them. This study aims to classify the various forms of NFT scams based on their juridical and technological characteristics, and to assess the adequacy of existing legal instruments in Indonesia, including criminal fraud provisions, consumer protection laws, electronic transaction regulations, and intellectual property rights. The research employs normative legal methods, focusing on statutory and conceptual approaches, as well as an examination of global practices in digital asset regulation. The analysis reveals a regulatory gap, particularly concerning marketplace liability, smart contract due diligence mechanisms, and cross-jurisdictional law enforcement. Therefore, the establishment of a specific regulatory framework that is risk-based, technologically adaptive, and oriented toward digital consumer protection is necessary.